2007
DOI: 10.1063/1.2786032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of collisions on dust particle charging via particle-in-cell Monte-Carlo collision

Abstract: In this paper, the effect of collisions on the charging and shielding of a single dust particle immersed in an infinite plasma is studied. A Monte-Carlo collision (MCC) algorithm is implemented in the particle-in-cell DEMOCRITUS code to account for the collisional phenomena which are typical of dusty plasmas in plasma processing, namely, electron-neutral elastic scattering, ion-neutral elastic scattering, and ion-neutral charge exchange. Both small and large dust particle radii, as compared to the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Thus, neither OML nor ABR models are able to describe the dependence of the particle floating potential on plasma collisionality. At the same time, over the last several years there have been a number of investigations, including theories, experiments, and simulations, which clearly demonstrated that the largest variations in α (about one order of magnitude in some cases) can be associated with the plasma collisionality level [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. The qualitative picture of the variation of the normalized potential α with plasma collisionality emerging from these studies is sketched in Fig.…”
Section: Particle Chargingmentioning
confidence: 99%
“…Thus, neither OML nor ABR models are able to describe the dependence of the particle floating potential on plasma collisionality. At the same time, over the last several years there have been a number of investigations, including theories, experiments, and simulations, which clearly demonstrated that the largest variations in α (about one order of magnitude in some cases) can be associated with the plasma collisionality level [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. The qualitative picture of the variation of the normalized potential α with plasma collisionality emerging from these studies is sketched in Fig.…”
Section: Particle Chargingmentioning
confidence: 99%
“…Single dust grain simulations have investigated in detail the charging of the dust grain [6][7][8] , wake potential 4,[9][10][11] and the influence of the surrounding plasma properties like pressure 9,12 , ion speed 8,13,14 , charge exchange 12,[15][16][17] and inhomogeneties in the plasma sheath 9,18 . In twoparticle chains it has been found numerically that the negative charge of the downstream grain is reduced because the ion focus of the upstream grain increases the ion current onto the grain 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier versions of the DEMOCRITUS code (or of CELESTE2D from which DEMOCRITUS descends) were used in numerous previous studies [1,41,27,40,[42][43][44]. The changes presented here are sufficiently deep to require a rebenchmarking and only new original results are reported below.…”
Section: Applicationsmentioning
confidence: 91%